The Spermine Phosphate-Bound Cyclooctaoxygen Sodium Epigenetic Shell of Euchromatin DNA Is Destroyed by the Epigenetic Poison Glyphosate - Kesel, Andreas J (Archives of Clinical and Biomedical Research, 2023)
Oxygen exists in two gaseous (dioxygen and ozone) and six solid allotropic modifications. An additional allotropic modification of oxygen, the cyclooctaoxygen, was predicted to exist in 1990. The first synthesis and characterization of cyclooctaoxygen as its sodium crown complex, isolated in the form of three cytosine nucleoside hydrochloride complexes, was reported in 2016. The sperminium hydrogen phosphate/cyclooctaoxygen sodium complex was calculated to cover the actively transcribed regions (2.6%) of bovine lymphocyte interphase genome. Cyclooctaoxygen seems to be naturally absent in hypoxia-induced highly condensed chromatin, taken as a model for eukaryotic metaphase/anaphase/early telophase mitotic chromatin. Hence, it is proposed that the cyclooctaoxygen sodium-bridged sperminium hydrogen phosphate and selenite coverage serves as an epigenetic shell of actively transcribed gene regions in eukaryotic ‘open’ euchromatin DNA. Cyclooctaoxygen sodium-bridged sperminium hydrogen selenite was calculated to serve as a marker shell component at ATG start codons in human euchromatin DNA mRNA genes, both at the translation initiation triplet and at 5′-untranslated region upstream ATGs. The total herbicide glyphosate (ROUNDUP®) and its metabolite (aminomethyl)phosphonic acid (AMPA) are proved to represent ‘epigenetic poisons’, since they both selectively destroy the cyclooctaoxygen sodium complex. This definition is of reason, since the destruction of cyclooctaoxygen is certainly sufficient to bring the protection shield of human euchromatin into collateral epigenetic collapse. The total herbicide glyphosate and its environmental metabolite (aminomethyl)phosphonic acid (AMPA) can be associated in vitro with catalytic detoriation of eukaryotic euchromatin genetic information. The epigenetic shell of eukaryotic euchromatin is susceptible to decay induced by catalytic epigenetic poisons threatening eukaryotic genomic heritage.